Hematological, biochemical, and endocrine parameters in acute response to increasing-intensity exercise in Colombian Paso horses (2021)
ABSTRACT: The present study aimed to describe the hematological, biochemical, and endocrine parameters in acute response to increasing-intensity exercise in Colombian Paso horses (CPHs). A standardized field exercise test was carried out on 11 untrained adult CPHs of both sexes. The variables of interest were measured before and after the test (i.e. hematocrit, total plasma proteins, creatine kinase, creatinine, blood urea nitrogen —BUN, aspartate aminotransferase, gamma glutamyl transpeptidase, triglycerides, cholesterol, alkaline phosphatase, cortisol, insulin, blood sugar levels). Evidence of sympathetic-adrenergic response activation, described for other breeds and equestrian sports disciplines (i.e. hemoconcentration, negative change in plasma volume, slight increase in creatinine and BUN) was found. In addition, evidence of mobilization and use of energy sources such as glucose and triglycerides was found. In conclusion, the increasing-intensity exercise carried out during a standardized field test produced a negative change in plasma volume and the activation of the classic sympathetic-adrenergic response in CPHs.